2015
DOI: 10.1186/s13000-015-0346-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of recurrent papillary thyroid cancer

Abstract: BackgroundTo investigate the clinicopathological features of recurrent papillary thyroid carcinoma (PTC).MethodsA retrospective analysis on clinical and pathological data of 34 patients with recurrent PTC was carried out. A total of 281 patients with non-recurrent PTC during the same time period were chosen as the control group.ResultsPatients were divided into three groups according to the pathological subtype. The number of patients belonging to Groups 1, 2, and 3 were 28, 154, and 133, respectively. 78 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrent PTC mainly refers to local and distant recurrence, including recurrence of primary tumor, lymph node metastases, invasion of the esophagus and trachea, invasion of muscles, nerves and distant metastases. Many factors could affect the recurrence of thyroid cancer, and 20% PTC patients relapse after treatment and require reoperation (7)(8)(9). Consequently, analyzing the molecular characteristics of PTC and exploring new targets for therapy have been major clinical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicated that the most invasive variants of PTC are: diffuse sclerosis variant (DSV), tall cell variant (TCV), columnar cell variant (CCV), solid variant (SV), and hobnail variant (HV). These variants are generally closely related to higher recurrence and metastasis rates and have low sensitivity to chemotherapy and radioactive iodine therapy, and the survival rate may also be low [1] [25] [33] [35]- [41]. Finally, we compared the biological characteristics of tumor cells in primary thyroid carcinoma and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%